Trends in Trust in Public Institutions in Hungary 2017-2023 - Budai, Balazs Benjamin; Bozso, Gabor; Csuhai, Sandor; Tozsa, Istvan (Journal of Ecohumanism, 2024)
The trust in governments is a topical issue today in good governance context. Three national representative primary surveys of similar methodology and size were compared: one in 2017, one in 2020 and one in 2023. Our present study focuses on a segment of these surveys, the evolution of trust and its situation in 2023 for three groups of public institutions. We have not only surveyed the trend in trust, but also several demographic factors to answer the reasons for the change. We have examined the evolution of trust by age, educational attainment, frequency of internet use and the location and type of the respondent's municipality. This gave a trend over six years, which can be indicative for policy makers: the trend is downwards on the nationwide average, but there are positive exceptions. The present survey allows us to identify which institutions, areas and users have improved and which have tainted in terms of public confidence. The degree of change is to determine the urgency of intervention.